2014
DOI: 10.1007/s00431-014-2425-0
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography is useful for ruling out fractures in paediatric emergencies

Abstract: The high negative predictive value of infrared thermography suggests that it is a promising method for ruling out fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…The study by Lasanen et al suggested that inflamed joints had higher regional temperatures, whilst in the study involving paediatric fracture, Sanchis-Sánchez et al showed such pathology could be detected by identifying areas of increased skin temperature [16,17]. Conversely, a study into sports injuries and muscle strains found particular injuries to be associated with a localised decrease in temperature, so further research into this application of IRT may be necessary [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Lasanen et al suggested that inflamed joints had higher regional temperatures, whilst in the study involving paediatric fracture, Sanchis-Sánchez et al showed such pathology could be detected by identifying areas of increased skin temperature [16,17]. Conversely, a study into sports injuries and muscle strains found particular injuries to be associated with a localised decrease in temperature, so further research into this application of IRT may be necessary [28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IRT has been successfully applied to the diagnosis of varying degrees of paediatric skin burn, with a reported sensitivity and specificity often greater than that of clinical assessment [14,15]. Recent pilot studies have shown that IRT can have other applications in paediatric emergency medicine, in screening for specific conditions such as fracture and joint inflammation, as well as monitoring wounds for signs of healing or infection [15][16][17][18]29]. In a prospective study of 51 children presenting with unilateral limb injury, the radiographs and thermal images were analysed; 11 showed fracture on radiograph, of which, 7 (64%) were matched by thermal imaging [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the remote recording does not interfere with sweat evaporation that is a major driver of hypoglycaemic Ts responses. The approach has proven useful in assessing Ts changes associated with regional anaesthesia [20,21], and has been suggested in ruling out fractures and monitoring vascular malformations, haemangiomas, burns and wound infections [22,23]. With the use of thermal images we are able to show changes in Ts in relation to a blood glucose level of 2.0-2.5 mmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic disorders that begin in childhood, such as type 1 DM, vascular disturbances manifesting as skin temperature changes have been found . Infrared thermography has also been used to assess scleroderma , hemangiomas, vascular malformations, burns , digit amputations, extremity thrombosis, abscesses, fractures and wound infections in the paediatric population .…”
Section: Introductionmentioning
confidence: 99%